(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This paper aims to offer teachers of English for Specific Purposes (ESP) a comprehensive overview of how newspapers can serve as an effective resource for teaching Business English. The primary objective is to help students achieve proficiency in Business English by engaging with the business section of English-language newspapers.